2011
DOI: 10.1002/jcla.20464
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid‐A levels in neonatal necrotizing enterocolitis

Abstract: We aimed to evaluate serum levels of serum amyloid-A (SAA) both in the diagnosis and monitoring the treatment response of necrotizing enterocolitis (NEC). Forty-five preterm neonates were enrolled in the study, including 15 infants with NEC, 15 with sepsis, and 15 healthy preterm infants. Pre- and posttreatment serum SAA levels were measured. Among patients with NEC, 11 had stage 1 and 4 had stage 2 disease according to the modified Bell's staging criteria. Baseline SAA levels of the infants with NEC were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Eight upregulated proteins were associated with samples at NEC diagnosis and four different proteins were associated with LOS diagnosis. In accordance with previous studies, upregulation of C-reactive protein and serum amyloid A were associated with the diagnosis of NEC ( 7 , 8 , 9 , 18 ). Here, C-reactive protein was upregulated in all NEC patients at diagnosis and exceeded the average for controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eight upregulated proteins were associated with samples at NEC diagnosis and four different proteins were associated with LOS diagnosis. In accordance with previous studies, upregulation of C-reactive protein and serum amyloid A were associated with the diagnosis of NEC ( 7 , 8 , 9 , 18 ). Here, C-reactive protein was upregulated in all NEC patients at diagnosis and exceeded the average for controls.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work in preterm biomarker research has used targeted approaches, identifying many potential biomarkers including intestinal fatty acid–binding protein, serum amyloid A, and C-reactive protein that have been used alone or in combination, but with little impact to date on clinical care ( 7 , 8 , 9 ). A recent metabolomic pilot study showed that changes in the serum metabolome prior to NEC are associated with upregulation of interleukin-1β (IL-1β), although this study involved only five patients (10 samples) with NEC and sample timing in relation to NEC was quite varied ( 10 ).…”
mentioning
confidence: 99%
“…Recently, Ng et al reported that plasma SAA is a promising marker for the detection of NEC [16]. Furthermore, SAA in plasma has been reported to positively correlate with NEC stage [4], [24], [25]. In these studies, only the difference between Bell stages was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It may be questionable whether Bell stage I represents actual NEC, as no intestinal pneumatosis is present in this stage, however the results indicate an association between SAA levels and NEC stage. Eras et al found elevated SAA levels in plasma in higher Bell stages at time of NEC diagnosis [25]. Urinary SAA has not been used previously to assess the severity of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…78 Mean serum SAA is increased in preterm infants with NEC as compared to those with sepsis alone. 80 Serum SAA could distinguish infants with NEC from those with sepsis and that levels were greater in Bell's stage II/III versus those with stage I. 80 Serum SAA could distinguish infants with NEC from those with sepsis and that levels were greater in Bell's stage II/III versus those with stage I.…”
Section: Serum Amyloid Amentioning
confidence: 99%